The Effect of Compensation, Knowledge Management, and Benefits on Employee Performance - Djunaedi Djunaedi; Dipa Teruna Awaludin (Indonesian Journal Economic Review (IJER), 2026)
This study aimed to investigate the impact of compensation, knowledge management, benefits, and motivation on employee performance at BSI KC Pandanaran Semarang. The study targeted employees of BSI KC Pandanaran Semarang, with a total of 108 respondents participating in the research. A causal research design was employed, utilizing SPSS 26 software for instrument testing and descriptive analysis to assess the data. The results revealed that compensation, knowledge management, benefits, and motivation each have a significant influence on employee performance at BSI KC Pandanaran Semarang. These findings suggest that a well-structured compensation system, efficient knowledge management practices, attractive benefits, and high levels of motivation can enhance employee performance. The research provides valuable insights for management to design policies that foster a conducive environment for improving employee performance, ultimately benefiting the organization. Based on the outcomes, it is recommended that the company continuously review and improve these factors to sustain and enhance employee productivity and job satisfaction.